The development of an IoT-based air quality monitoring system using the Blynk application / Nurzaid Muhd Zain ... [et al.] - Muhd Zain, Nurzaid; Mohd Rozi, Muhammad Amir Rusyaidi; Othman, Mahfudzah; Paidi, Zulfikri (UiTM Cawangan Perlis, 2024)
This paper discusses designing and developing an Arduino-based air quality monitoring system utilizing the Blynk application. The aim is to design an IoT-based air quality monitoring system that allows users to check current air quality precisely and promptly via their mobile phones in real-time. The construction of the application involves three phases: design, prototype development, and system testing. The design and development phases involved various setups and configurations of MQ135 gas sensor and microcontroller NodeMCU to assess air quality in parts per million (ppm) and allow data transmission via Wi-Fi to users’ mobile phones with the Blynk application. System testing has shown accurate results in the MQ135 gas sensor among five different gases, which led to the efficiency of the prototype system in detecting air quality based on air quality level (ppm). As a result, the Red LED illuminates, and the Buzzer emits a warning sound when the air pollution level exceeds 150ppm.